Prenatal ultrasonographic findings of esophageal atresia: potential diagnostic role of the stomach shape - Chi-Son Chang; Yunsun Choi; Seo-yeon Kim; Cheonga Yee; Mina Kim; Ji-Hee Sung; Sanghoon Lee; Suk-Joo Choi; Soo-young Oh; Jeong-Meen Seo; Cheong-Rae Roh (Korean Society of Obstetrics and Gynecology, 2021)
Objective We investigated prenatal sonographic characteristics of esophageal atresia (EA) with advancing gestation. We focused on the degree of polyhydramnios and the stomach shape. Methods This study included 27 EA cases (EA group) and 81 idiopathic polyhydramnios cases (non-EA group). The non-EA group consisted of cases without any fetal structural anomaly, musculoskeletal disorder, chromosomal abnormality, or maternal diabetes. Both groups included only singleton pregnancies. Amniotic fluid index (AFI) and width/length (W/L) ratio as well as the product of width and length (W×L) of stomach were serially assessed during gestation and compared between the 2 groups. To predict EA using W/L ratio and W×L, receiver operating characteristic curve analysis was performed. Results Polyhydramnios was evident in 77.8% of EA cases. We observed 25.9% and 22.2% EA cases with an absent stomach and a small visible stomach, respectively. After 28 weeks, the EA group manifested significantly higher AFI than the non-EA group. After 32 weeks, W/L ratio in the EA group tended to be lower than that in the non-EA group (32-36 weeks: 1.36 vs. 1.72, P=0.092; >36 weeks: 1.43 vs. 1.63, P=0.024). To predict EA, the calculated area under the curve for W/L ratio was 0.651 after 32 weeks. The diagnosis of EA using a cut-off value of W/L ratio <1.376 showed sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio to be 84.6%, 52.9%, 1.796, and 0.081, respectively. Conclusion A low W/L ratio of stomach after 32 weeks with progressive idiopathic polyhydramnios may be used to predict EA.